Diaphragmatic and Rectus Femoris Muscles Ultrasonography in Relation to Motor and Respiratory Functions in Ambulatory Boys with Duchenne Muscular Dystrophy - Hassanein, Sahar M.A.; Elagouza, Iman; Sakr, Hossam; Mohammed, Maha Z.; Rihan, Ahmed; Deifalla, Shaymaa (Journal of Pediatric Neurology, 2023)
Our aim was to establish correlations between GSGC (Gait, Stairs, Gower, Chair) scores and ultrasonographic (US) findings of rectus femoris muscle (RF) and to study correlation between pulmonary function tests (PFT) and diaphragmatic muscles thickness in ambulatory boys with Duchenne muscular dystrophy (DMD). Twenty-four ambulatory boys with DMD were included. Their motor functions were assessed using GSGC scale. All the participants underwent PFT. US was used to assess RF quantitatively (gray scale analysis) and semiquantitatively (modified Heckmatt score) besides assessment of diaphragmatic muscle thickness. Patients with grade IV modified Heckmatt scale had the worst functional performance compared with grade III and II evidenced by having the highest total GSGC score (p < 0.01), worst gait, stairs climbing, chair rising scores, and the longest time for rising from floor (p < 0.05). A significant positive correlation was detected between forced expiratory volume in 1s/ forced vital capacity and right diaphragmatic muscle thickness. GSGC score positively correlated with RF US findings (quantitative gray scale analysis). GSGC score is a successful tool that could be used for clinical evaluation of patients with DMD. Diaphragmatic US introduces an option for screening and monitoring of restrictive respiratory pattern in patients with DMD after determining the reference values of diaphragmatic muscle thickness in different ages.
Keywords: Duchenne Muscular Dystrophy; GSGC scores; quantitative (gray scale analysis); semiquantitative Heckmatt grading scale; ultrasonographic diaphragmatic thickness